ANALISIS SPC PADA PRODUKSI GENTENG DI UD. GENTENG MANTILI SDH KABUPATEN PRINGSEWU - Yosijanuardi, Yosi; Ayudyah Eka Apsari (Jurnal Cakrawala Ilmiah, 2024)
Problems in the production process at UD. Mantili Tile Sdh Pringsewu District caused losses to the company and customers. From January to December 2023, the product defect rate reaches 13%, while the allowable production defect tolerance limit is 7%. This high level of defects contributes to an increase in production costs. Therefore, this research is expected to reduce the level of production defects. Many factors cause defects, such as raw material quality, human error, and poor equipment condition, affecting productivity and product quality. By using the Statistical Process Control (SPC) method, it is expected to reduce the defect rate, identify the type of damage, and categorize the factors causing product defects. Data processing using pareto charts shows that fracture defects are the most dominant with a percentage of 53.1%, followed by crack defects at 46.9%. Analysis with fishbone diagrams reveals that the causative factors of disability consist of three main elements: human, material, and method